E-Modules Through Flipped Classroom and PBL Models on Environmental Pollution Material to Increase Problem-Solving Ability - Dwi Novita, Ria; Tien Aminatun; Rihab Wit Daryono (Journal of Education Technology, 2022)
The lack of educator knowledge regarding technology, information, and the use of learning media can increase learning boredom which causes students to lack understanding of the material presented by the teacher. So there needs to be innovation in order to have a positive impact on students by using the media. This study aims to develop an android mobile-based e-module on environmental pollution material. This type of research is development. Research using research and development methods. The test subjects were 72 students. The sampling technique uses probability sampling with the simple random sampling method. The methods used to collect data are interviews, questionnaires, and tests. The instruments used to collect data were interview sheets, questionnaires, and test questions in testing the effectiveness of the e-module using a quasi-experimental non-equivalent pretest-posttest control group design. The results of the research stated that using Android-based e-modules was appropriate for learning environmental pollution material. It was concluded that the e-module based on android mobile could improve the problem-solving skills of Class X high school students in biology subjects. Android-based e-modules can help students learn.